Preparation of poly(glycidyl methacrylate) grafted sulfonamide based polystyrene resin with tertiary amine for the removal of dye from water - Senkal, Bahire Filiz; Bildik, Fatih; Yavuz, Erdem; Sarac, Ayfer (ELSEVIER, 2007)
Poly(glycidyl methacrylate) was grafted onto crosslinked poly (styrene) beads through the 2-chloroethyl sulphonamide (CSA) groups present in the resin using ATRP polymerization method. A beaded polymer with a poly (glycidyl methacrylate) surface shell was prepared in three steps, starting from poly (styrene-DVB) (10% crosslinking) based beads with a particle size of 420-590 mu m, according to the synthetic protocol; chlorosulfonation, sulfamidation with 2-chloroethylamine hydrochloride and grafting reaction of poly (glycidyl methacrylate). The polymeric resin was prepared with 147.8% of grafted glycidyl methacrylate and subsequent modified with diethyl amine to introduce tertiary amine groups. This resin has also been demonstrated to be an efficient dye sorbent, able to remove dye from water even at ppm levels. The dye sorption capacity under non-buffered conditions is around 0.90 g dye/g resin. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: ATRP; graft polymer; poly(glycidyl methacrylate); dye removal; polymeric sorbent; TRANSFER RADICAL POLYMERIZATION; SI-ATRP; SURFACE; BRUSHES; FUNCTIONALIZATION; PARTICLES; FILMS; IONS; Chemistry; Engineering; Polymer Science